Konsep Hak Ekonomi dan Hak Moral Pencipta Menurut Sistem Civil Law dan Common Law - Hendra Tanu Wijaya (Fakultas Hukum Universitas Islam Indonesia, 2003)
Copyright is the legal protection extended to the owner of rights in an original work that he has created. It comprises two main sets of rights: the economic rights and the moral rights. The economic rights are the rights to obtain the economic-benefits derived from the copy right work as well as from the related right work. Conversely, the moral rights include the author's right to object any distortion, mutilation or other modification of his work that right be prejudicial to his honor orreputation. The concept of copyright was originally from the legal system of the continent, the civil law countries such as French and German focus exclusively on individual copyright work, whereas the common law countries like the United States of America and England focus on the ownership of copyright works.